Is ‘Miracle’ an Intelligible Notion? - Miller, John Franklin (Scottish journal of theology, 1967)
That Christians must believe in miracles is indubitable, for their religion substantially rests upon the miracle of the resurrection. However there have been a number of criticisms of miracles as both unintelligible and unreasonable. This paper will attempt to answer these criticisms and to show that the notion of ‘miracle’ is intelligible and that to believe in miracles is reasonable.1 To do this, the following four criticisms must be answered in some way:(1) The very concept of ‘miracle’ is a self-contradictory or in some other way incoherent notion.(2) The empirical evidence given for miracles has always been inadequate to substantiate a rational belief.(3) Judging from past experience, one can always rule out even the possibility of miracles.(4) A miracle can never be shown incapable of a natural and scientific explanation, at least in principle.